COVID-19: impact on ostomy and continence care - Karen Spencer, & Stacy Haddad and & Renee Malandrino & (WCET Journal - French Edition, 2020)
Introduction  The COVID-19 pandemic has changed our world. It has impacted all healthcare professionals (HCPs), organisations and the people they serve in multiple ways. This includes the specialty area of nursing in ostomy and continence care. During this time, it is important to know what can be done to support clinicians and patients (end users) through understanding what they are experiencing and how they are adapting to this pandemic. Objective  To gather research which describes the impact COVID-19 has had on clinicians and people with an ostomy or intermittent catheterisation requirements. Methods  The research was conducted virtually to keep patients, clinicians and researchers safe but enable important learnings. Research modalities utilised were surveys and an observational study. Results  This COVID-19 research shows that 57% of ostomy end users in the US and UK report peristomal skin issues in the past month. What has caused more concern is that 84% of ostomy end users report NOT contacting a HCP about their skin issues. In continence care, 49% of intermittent catheter (IC) users are more concerned about urinary tract infections (UTIs). Despite these challenges, many ostomy end users (52%) and IC end users (37%) report not knowing if telehealth is an option for their care. Instead, this research shows that end users are accessing more information online – ostomy end users increased their online usage by 34% and IC end users by 50%. Both groups report the information they are seeking the most are tips for troubleshooting issues and information about the availability of their ostomy and continence products. This matches the ostomy nurse survey results that indicate clinicians are seeking information on ostomy education and product availability. Conclusion  Early research suggests that ostomy and continence care patients alike are being negatively impacted by the COVID-19 pandemic. As this is only the beginning of the global pandemic, much more research is needed.